Newborn pulse oximetry screening: A review. (June 2022) - Kirk, Akrishon; Webb, Amanda; Rodriguez-Prado, Yahdira M.; Dorotan-Guevara, Maria
Abstract: Background: Neonatal pulse oximetry screening in combination with prenatal assessment and physical examination has increased the detection rate of critical congenital heart defects in babies to up to 96% before being discharged from the hospital. Aim of review: A review of the key concepts of this screening tool with highlight on the primary care physician's role is presented in this article. Key scientific concepts of review: Critical congenital heart disease requires intervention in the first year of life. Pulse oximetry screening is a cost effective, painless, moderately sensitive, and highly specific screening tool for early detection of critical congenital heart disease. Pulse oximetry screening has an overall sensitivity of 75% and specificity of 99.3% and when combined with physical exam and antenatal testing, sensitivity increases to over 90% [9]. Special considerations for critical congenital heart disease screening should be given in patients in the neonatal intensive care unit, at high altitudes, and born outside of hospitals. Highlights: Pulse oximetry is an easy, cost effective, painless, way to screen for critical congenital heart defects Neonatal pulse oximetry screening combined with prenatal assessment and physical exam increases detection of critical congenital heart defects to 96% Special consideration should be taken when using pulse oximetry outside of the hospital, in high altitude, and in the neonatal intensive care unit Primary care providers play an integral role in identifying critical congenital heart defects not found on screening